The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acschembio.5b00787
|View full text |Cite
|
Sign up to set email alerts
|

Design of Potent and Proteolytically Stable Oxyntomodulin Analogs

Abstract: Incretin-based peptides are effective therapeutics for treating type 2 diabetes mellitus (T2DM). Oxyntomodulin (OXM), a dual agonist of GLP-1R and GCGR, has shown superior weight loss and glucose lowering effects, compared to single GLP-1R agonists. To overcome the short half-life and rapid renal clearance of OXM, which limit its therapeutic potential, both lipid and PEG modified OXM analogs have been reported. However, these approaches often result in reduced potency or PEG-associated toxicity. Herein we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 37 publications
(73 reference statements)
0
37
0
Order By: Relevance
“…administration and a half-life of 2-3 h after s.c. administration in humans (34). Previously, we showed that one could staple two turns of the alpha-helix of oxyntomodulin with a biaryl cross-linker to improve potency and half-life (35). We have further developed this approach with a novel, tunable staple engineered with a serum protein binding motif to significantly improve the potency and serum half-life of the stapled peptide.…”
Section: Resultsmentioning
confidence: 99%
“…administration and a half-life of 2-3 h after s.c. administration in humans (34). Previously, we showed that one could staple two turns of the alpha-helix of oxyntomodulin with a biaryl cross-linker to improve potency and half-life (35). We have further developed this approach with a novel, tunable staple engineered with a serum protein binding motif to significantly improve the potency and serum half-life of the stapled peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Alkene RCM on peptides was first reported b9y Blackwell and Grubbs, who reported solution‐phase metathesis and ensuing hydrogenation of i to i +4 systems to generate paraffinic staples . Stapling between the i to i +7 positions was also pursued, such as in the stabilization of oxyntomodulin analogues through biaryl crosslinking of two cysteine residues . By introducing azide‐ and alkyne‐terminated amino acids into the sequence, copper‐catalyzed azide–alkyne cycloaddition (CuAAC) has also been successfully adapted to peptide stapling by a number of research groups (Figure ) …”
Section: Figurementioning
confidence: 99%
“…Thus, it is necessary to produce long-lasting analogues for clinical use. As discussed above, the substitution of the naturally occurring -Ala at position 2 in incretin results in DPP-IV resistance, and the C-terminal PEGylation and fatty acid derivatization of incretins results in reduced renal clearance by which several long-acting OXM analogues have been successfully developed (Muppidi et al, 2016). Indeed, a recent study of six novel OXM analogues has revealed that OXM-based peptides with specific N-terminal position 2 modifications are stable and show particular promise for the treatment of diabetes (Lynch et al, 2014).…”
Section: Oxm and T2dmmentioning
confidence: 99%